Too Good to Be True?: Reckoning with Sensational Inscriptions - Rollston, Christopher A. (The Biblical archaeology review, 2024)
From time to time, the world of biblical archaeology is upended by the discovery of a remarkable inscription. But is it possible that our insatiable appetite for such groundbreaking finds clouds our ability to evaluate them cautiously and fairly? A closer look at a few recent examples sheds light on how our eagerness to find the sensational can lead even experts to jump to inaccurate conclusions.